Assessment of technology vs environmental regulations in China based on DEA malmquist model and porter hypothesis - Zhang, Xiaojie; Yue, L.; Chang, Y.; Wu, Z.; Muhammad, Amran A. (ALÖKI Applied Ecological Research and Forensic Institute, 2018)
Serious environmental pollution due to the economic boom in China has forced the government to implement environmental regulations. This paper examines the relationship between environmental regulations and technological development in different regions of China. Industry data from 1999 to 2012 using the DEA (Data Envelopment Analysis)-Malmquist productivity index were analyzed. It was found that total productivity growth is mainly caused by the change in technological progress. The environmental regulations of industry had a positive effect on technical progress at the national level. However, the relationship between environmental regulation and technological progress showed significant differences at the regional level. Results showed that for every 1% increase in strength of environmental regulation, there was a corresponding 7.04% increase in technology progress in eastern China. However, in central and western China, results showed that for every 1% increase in strength of environmental regulation, technology progress declined by 4.91% and 1.08%, respectively. It is concluded that the Porter hypothesis is well supported by data from the advanced eastern regions, while not fully supported by data from the underdeveloped central and western regions. For the central and western regions, various reasons for deviation from the Porter Theory have been determined by using the Environmental Kuznets Curve (EKC). Policy implications such as using government allowances and bank loans to import well educated staff, to enhance production technologies, to implement environmental solutions, and to set up strict regulations are recommended for the policy makers.